Accountability and Management of Waqf: An Analysis of Waqf Practice in Banda Aceh, Indonesia - Ali, Ahmad Syihan; Fahlevi, Heru; Saputra, Mulia (Universitas Syiah Kuala, 2019)
AbstractObjective This research was conducted to analyze how management, regulation, recording, and reporting of waqf assets in Banda Aceh, IndonesiaDesign/methodology This research is a qualitative-descriptive type study. Data collection techniques utilize the method of observation, interview, and documentation techniques. The data analysis model used in this study is the miles model and interactive interaction.Results The results of the study indicate that the implementation of the law is not optimal and not fully in accordance with the management of waqf assets in Banda Aceh. Weak accountability was also evident in the accounting and reporting of waqf assets in Banda Aceh City.Research limitations/implications This study is limited as it only focuses on asset management carried out by manager of waqf (Nazhir Gampong) in the Banda Aceh City administration, not yet in the realm of management carried out by foundations and organizations. Therefore future studies are suggested to fill the limitations of this study.